Genetic Characteristic of Dominant Ultra Short Stem and Wax Coating Absence for Winter Rye (Secale cereale L.) - В. В. Скорик; Волод. В. Скорик; Н. В. Симоненко; О. П. Скорик (Plant Varieties Studying and Protection)
By means of directed hybridization and selection, a new donor of Winter Rye with combination of ultra short stem and absence of wax coating has been synthesized. Markings was offered for the first time for dominant genes of ultra short stem characteristic – HI-3HI-3, and for recessive genes of absence of wax coating characteristic – wcwc. Determination is made of genetic variability, coefficients of inheritance, phenotype and genotype correlation coefficients, on the basis of which a selection strategy by ten quantitative characteristics is proposed. Polypheny and cohesion effects were established. Under certain conception, strategy and tactic of improvement by breeding of Winter Rye characteristics, determination of genetic and statistic parameters between traits of parents and the offspring is required.